EPISTEMOLOGI ISLAM DAN BARAT - ALI IMRAN SINAGA (Universitas Islam Negeri Sumatera Utara Medan, 2017)
Islam has a specialty in the development ofepistemologies in the world. Character kewahyuan it has alreadyable to defend the truth which it offers.A marriage of science methods and good behavior isthe main objective to get to know God,as God The Almighty One. Kata Kunci: Epistemologi, Islam, Barat.